The effect of competition on salivary testosterone in elite female athletes - Hamilton, L. D.; van Anders, S. M.; Cox, D. N.; Watson, N. V. (International Journal of Sports Physiology and Performance, 2009)
The association between androgens and competition in women has been understudied compared with men. The current study examined the link between testosterone (T) and competition in elite female athletes, using a sample of female wrestlers that included athletes competing at both the national and international level. In a repeated-measures design, saliva samples were collected before and after wrestling bouts, with comparable samples of wins and losses, and subsequently analyzed for T. Study results showed a 22% increase in circulating bioavailable T from pre- to postbout, F(1, 12) = 9.71, P = .009. There was no significant difference in T between win or loss outcomes. These findings - showing a link between individual head-to-head competition and T in women - demonstrate that women`s androgenic responses to environmental contexts are dynamic and may be an important factor to address in research on competitive performance.